Perfil dos doentes de tuberculose nos anos de 2007-2008 no Departamento da Regional de Saúde III no Estado de São Paulo - Caliari, Juliano de Souza (Universidade Federal de São Carlos, 2009)
The Heart Region, situated in the State of São Paulo, stands out for showing good indicators of quality of life, numbers of health establishments that exceeds the state average, besides being part of a modern system of information registering, the TBWEB, which facilitates the data entry and the monitoring of the TB patient. However, studies point that the most TB cases in the region that are referred to specialized hospitals still show a classic form and treatment of TB, that could be monitored in the ambulatories of their own cities. Considering the health and information support network and the good indicators of quality of life shown, it is noticed that it is still known a little about the TB patients profile and the kind of health assistance offered to them in the region. The objective of this study was characterizing the TB patients epidemiological profile that were notified in the region, as well as knowing the flow and the health network for their diagnosis and treatment. This was a descriptive and quantitative study which, in its first stage, the TBWEB database of the 2007 and 2008 years was analyzed, and in its second stage, interviews with the Tuberculosis Control Program (PCT) responsible ones in the six cities of the region were realized. The number of identified patients was 122, and between them there were 84 men with average age of 40 years. About 50% showed a schooling degree between 0 and 7 years. The pulmonary form was responsible for 86% of the cases; 85% were new cases and 25% of the notifications were done in hospitals and emergency units. The alcoholism (24%) and AIDS (18%) were the most present comorbidities, and the social causes, the diagnostic elucidation and the non-adherence to the treatment were the most found reasons of internment. For diagnosis, 101 radiographs, 94 bacilloscopies and 25 expectoration cultures were used. The Scheme I was used in 82% of the patients and 53% of them finished the card showing cure. Regarding the attending flow, the cases, after identified, are notified and referred to the city A, where they will start the treatment. The professionals had pointed, as problems, the lack of support equipments such as vehicles, adequate physical space, supplies-, delay in doing tests and presenting its results, besides the lack of medical professionals with specific formation, staff training and active search for respiratory symptomatics. The positive characteristics were point as being the involvement between the staff and the community, the facility in requesting diagnostic tests and the easy access to the reference service. Therefore, it is noticed that the epidemiologic profile of this population is similar to the one described in the literature for the all the state, including a high rate of detection out of the basic attention. Although the PCT had been recommending, since the 1990 years, the decentralization of the TB care, the Heart Region still centralized the attending in a reference city, in the occasion of this study. The interviewed professionals recognize, as problems, the lack of physical structure and supplies, the delay in the flow of tests and its results, the lack of the staff training and active search, beyond justifying the centralization by the lack of specialist medical professional. They also recognize, as a facilitator, the link between the professional and the TB patient.
Profile of tuberculosis patients in the years 2007 2008 in the department of regional health III the State of São Paulo
Keywords: Tuberculose; Avaliação de programas; Projetos de Saúde Publica; Programas de saúde; CIENCIAS DA SAUDE::ENFERMAGEM